IDENTIFIKASI TANAMAN OBAT YANG DIMANFAATKAN OLEH MASYARAKAT DI DESA PERLIS KABUPATEN LANGKAT - Nadia Ananda; Adi Bejo Suwardi (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The use of traditional medicinal plants remains important in rural communities in Indonesia. This study aimed to identify medicinal plants used by the people of Dusun II Damai, Perlis Village, Brandan Barat District, Langkat Regency. The research was conducted through an exploratory survey using semi-structured and structured interviews with 10 respondents selected through snowball sampling. The results identified 15 medicinal plant species belonging to 12 families, with Zingiberaceae and Myrtaceae as the dominant families. Leaves were the most commonly used plant part, and boiling was the main preparation method. These plants were used to treat various diseases such as fever, colds, allergies, cough, stomachache, cholesterol, toothache, bloating, eye problems, and to reduce blood sugar levels. Local knowledge of medicinal plants should be documented and preserved.